Pengaruh Strategi Student Recap terhadap Hasil Belajar Anak di SMPN I Samudera - Masyura Masyura (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
The formulation of the problem in this study is whether the effect of the Student Recap (student overview) strategy on learning outcomes in pai at SMPN 1 Samudera? This study aims to determine the effect of the Student Recap (student overview) strategy on learning outcomes in pai at SMPN 1 Samudera. The population in this study were all class VII students of SMP Negeri 1 Samudera. Sampling used a purposive sampling technique consisting of two classes with a total of 43 students, namely class VII totaling 20 students and class VII-B totaling 23 students, for the experimental class, namely class VII-A being taught. The use of student recap strategies for the control class, namely VII-B class, is taught using conventional methods. This research is quantitative research and the instrument used is a test in both classes with the same shape and weight. Furthermore, the collected data were analyzed using the t-test at a significant level α = 0.05. From the results of data processing, it shows that the experimental class with X1 = 72 and S1 = 13.31. While the control class with X2 = 62.82 and S2 = 15.13 so that t count > t is 2.13 > 1.684, then HO is rejected, and Ha is accepted. In other words, the learning outcomes of students who were taught using student recap strategies were higher than students who were taught without using student recap strategies.